Hyoscine-N-butylbromide premedication on cardiovascular variables of horses sedated with medetomidine - Perotta, Joao H. [UNESP]; Canola, Paulo A. [UNESP]; Lopes, Maristela C. S. [UNESP]; Evora, Patricia M. [UNESP]; Martinez, Paulo E. B. [UNESP]; Escobar, Andre [UNESP]; Valadao, Carlos A. A. [UNESP] (Wiley-Blackwell, 2014)
Objective To evaluate the effects of intravenous (IV) or intramuscular (IM) hyoscine premedication on physiologic variables following IV administration of medetomidine in horses. Study design Randomized, crossover experimental study. Animals Eight healthy crossbred horses weighing 330 +/- 39kg and aged 7 +/- 4years. Methods Baseline measurements of heart rate (HR), cardiac index (CI), respiratory rate, systemic vascular resistance (SVR), percentage of patients with second degree atrioventricular (2oAV) block, mean arterial pressure (MAP), pH, and arterial partial pressures of carbon dioxide (PaCO2) and oxygen (PaO2) were obtained 5minutes before administration of IV hyoscine (0.14mg kg-1; group HIV), IM hyoscine (0.3mg kg-1; group HIM), or an equal volume of physiologic saline IV (group C). Five minutes later, medetomidine (7.5gkg-1) was administered IV and measurements were recorded at various time points for 130minutes. Results Medetomidine induced bradycardia, 2oAV blocks and increased SVR immediately after administration, without significant changes in CI or MAP in C. Hyoscine administration induced tachycardia and hypertension, and decreased the percentage of 2oAV blocks induced by medetomidine. Peak HR and MAP were higher in HIV than HIM at 88 +/- 18beatsminute-1 and 241 +/- 37mmHg versus 65 +/- 16beatsminute-1 and 192 +/- 38mmHg, respectively. CI was increased significantly in HIV (p0.05). Respiratory rate decreased significantly in all groups during the recording period. pH, PaCO2 and PaO2 were not significantly changed by administration of medetomidine with or without hyoscine. Conclusion and clinical relevance Hyoscine administered IV or IM before medetomidine in horses resulted in tachycardia and hypertension under the conditions of this study. The significance of these changes, and responses to other dose rates, requires further investigation.
Keywords: Blood gas analysis; Equine; Hyoscine; Medetomidine